2018
DOI: 10.1161/circulationaha.117.029622
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Actions of Fibroblast and Cardiomyocyte Smad3 Signaling in the Infarcted Myocardium

Abstract: In healing myocardial infarction, myofibroblast- and cardiomyocyte-specific activation of Smad3 has contrasting functional outcomes that may involve activation of an integrin/reactive oxygen axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
133
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(140 citation statements)
references
References 51 publications
3
133
0
4
Order By: Relevance
“…In contrast, neither the myofibroblastic phenotype nor the survival of cardiomyocytes were negatively affected. The cell‐type–specific death effect triggered by sCD74/MIF co‐treatment is in accord with previous studies that reported that the same stimuli or pathways can induce opposing effects in cardiomyocytes and fibroblasts 61, 62. That sCD74/MIF co‐treatment does not induce de‐differentiation of myofibroblasts supports our assumption that it is unlikely that sCD74/MIF‐activated downstream pathways simultaneously affect the death and de‐differentiation of myofibroblasts.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, neither the myofibroblastic phenotype nor the survival of cardiomyocytes were negatively affected. The cell‐type–specific death effect triggered by sCD74/MIF co‐treatment is in accord with previous studies that reported that the same stimuli or pathways can induce opposing effects in cardiomyocytes and fibroblasts 61, 62. That sCD74/MIF co‐treatment does not induce de‐differentiation of myofibroblasts supports our assumption that it is unlikely that sCD74/MIF‐activated downstream pathways simultaneously affect the death and de‐differentiation of myofibroblasts.…”
Section: Discussionsupporting
confidence: 92%
“…Because the adult mammalian heart has negligible regenerative capacity, repair of the infarcted myocardium is dependent on fibroblast activation and subsequent formation of a collagen‐based scar. Perturbations in fibroblast activation and in the profile of ECM proteins in the infarcted and remodelling myocardium can be associated with increased dysfunction and adverse remodelling (Frangogiannis et al, ; Kong et al, ). During the proliferative phase of infarct healing, the cardiac fibroblast population markedly expands (Frangogiannis et al, ).…”
Section: Myofibroblast Activationmentioning
confidence: 99%
“…Design of effective therapeutic strategies requires understanding of the relative role of Smad‐dependent and Smad‐independent signalling in vivo (Bujak et al, ; Rainer et al, ). In the infarcted heart, experimental studies have suggested distinct effects of Smad‐dependent signalling in cardiomyocytes and fibroblasts (Kong et al, ). Moreover, non‐Smad pathways may also contribute to activation of interstitial cells towards a fibrogenic phenotype (Molkentin et al, ).…”
Section: Targeted Anti‐inflammatory Interventionsmentioning
confidence: 99%
“…As a main downstream signal transducer of TGF-β1, SMAD3 is the most critical YAP/TAZ target transcription factor which can be phosphorylated by TGF-β1 and then promotes expression of target genes including type I and type III collagen which are the primary component of the extracellular matrix [40,41]. Of note, a recent study reveals that myofibroblast-and cardiomyocytespecific activation of SMAD3 has contrasting functional outcomes in healing myocardial infarction [42]. erefore, in our study, whether the regulatory role of QSG is reflected in cardiomyocytes or fibroblasts remains to be explored in subsequent studies.…”
Section: Discussionmentioning
confidence: 99%